The Psychological Conflicts of the Main and Secondary Characters of The Lady With The Dog - Ni Made Ayu Sintya Paramita Dewi; I Nengah Sudipa; A.A. Sg. Shanti Sari Dewi; Ni Made Ayu Widiastuti (CV. Ulil Albab Corp, 2023)
This study entitled The Psychological Conflicts of the Main and Secondary Characters of the